Simulation of multiposition direction finding systems for investigation of their working zones - Дем'янчук, В. С.; Коба, О. В. (Proceedings of National Aviation University (archive), 1999)
Worked out are the machine models for investigation of systems which determine the coordinates of objects by means of multiposition systems on the basis of angle-measuring instruments